Pandemic law – a roadmap for lege ferenda - Celso LEAL (Revista Jurídica Portucalense, 2022)
In recent years we have been ravaged by a pandemic that has changed the way of living and being in society, which has resulted in changes in lifestyle all over the world, has caused structural changes in the organization of services in the most varied sectors. Isolation was a necessity arising from the pandemic that was more difficult to accept, due to the fact that it limits fundamental rights, such as freedom, which gave rise to legal and public health debates. It was found that the pandemic should be governed by rules in view of the limitations it imposes on fundamental rights, as a way of protecting public health. The pandemic demonstrated the need to manage resources in view of the needs arising from the effects of the pandemic, as well as the need to adjust social and labor relations, a change in behavior and habits was imposed that implied restrictions on fundamental rights. Hence the need to legislate on the pandemic, as a way of protecting these events and thus having a normative instrument that supports the actions of States, both internationally and nationally. In Portugal, the need to create a health emergency law or pandemic law is debated, as a way of preventing and protecting the occurrence of pandemics and allowing the restriction of fundamental rights with constitutional protection.